Mycobacterium avium Modulates the Protective Immune Response in Canine Peripheral Blood Mononuclear Cells - Kim, Suji; Park, Hyun-Eui; Park, Woo Bin; Kim, Seo Yihl; Park, Hong-Tae; Yoo, Han Sang (Frontiers in Cellular and Infection Microbiology, 2021)
Mycobacterium avium, an opportunistic intracellular pathogen, is a member of the non-tuberculous mycobacteria species. M. avium causes respiratory disease in immunosuppressed individuals and a wide range of animals, including companion dogs and cats. In particular, the number of infected companion dogs has increased, although the underlying mechanism of M. avium pathogenesis in dogs has not been studied. Therefore, in the present study, the host immune response against M. avium in dogs was investigated by transcriptome analysis of canine peripheral blood mononuclear cells. M. avium was shown to induce different immune responses in canine peripheral blood mononuclear cells at different time points after infection. The expression of Th1-associated genes occurred early during M. avium infection, while that of Th17-associated genes increased after 12 h. In addition, the expression of apoptosis-related genes decreased and the abundance of intracellular M. avium increased in monocyte-derived macrophages after infection for 24 h. These results reveal the M. avium induces Th17 immune response and avoids apoptosis in infected canine cells. As the number of M. avium infection cases increases, the results of the present study will contribute to a better understanding of host immune responses to M. avium infection in companion dogs.